Study on the Optimization of the Tensile Properties of an Al-Li Alloy Friction Stir-Welding T-Joint - Yu Qiu; Yuansong Zeng; Qiang Meng; Wei Guan; Jihong Dong; Huaxia Zhao; Lei Cui; Xuepiao Bai; Mingtao Wang (Metals)
The softening of aluminum–lithium alloy welded joints generally leads to a reduction in mechanical properties. In this study, a piece of 2A97-T3 aluminum–lithium alloy with a thickness of 2.8 mm was selected as the test material, and the tool and process used for wire-filled stationary shoulder friction stir welding (SSFSW) were developed. By increasing the bearing area of the softening zone, an equal-strength T-joint was manufactured. Good weld formation was obtained when the rotation speed was set to 2000 rpm and the welding speed ranged from 100 to 120 mm/min. The thickness of the softening zone was controlled by adjusting the reserved gap between the shoulder and the workpiece. The softening mechanism of the weld joint was revealed. The softening was attributed to the coarsening of the main precipitated phases (T1 and θ′ phases) in the heat-affected zone (HAZ) and the dissolution of precipitated phases in the thermo-mechanically affected zone (TMAZ). Grain refinement in the nugget zone (NZ) led to a certain fine-grained strengthening effect, although the precipitated phase was almost completely dissolved. Due to the thermal effect of second-pass welding, the hardness value of the NZ and HAZ in the center of the skin further decreased, and the minimum hardness was approximately 70% that of the base material. Tensile testing results indicated that the softening effect was largely offset by the increased bearing area of the softening zone, resulting in the successful welding of high-strength Al-Li alloy T-joints with equal strength. The strength coefficient was found to be 0.977.